PH / GSH dual-responsive targeting nanoparticle based on MOF-199

By modifying hyaluronic acid on the surface of MOF-199 and wrapping with pH-sensitive polydopamine membrane, pH/GSH biresponsive targeting nanoparticles were constructed, which solved the problem of poor stability of MOFs in vivo, and achieved tumor targeting and Sustained release, improving the effect of chemotherapy.

CN119455009AInactive Publication Date: 2025-02-18WUHAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411561156.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The poor stability of existing MOFs in the body leads to insufficient specific accumulation of drugs at the lesion site and is easily eliminated by biomolecules.

Method used

Hyaluronic acid (HA) was modified on the surface of MOF-199, and a pH-sensitive polydopamine (PDA) membrane was used as the surface wrapping material for the drug carrier to construct pH/GSH biresponsive targeting nanoparticles.

Benefits of technology

It enhances the biocompatibility and structural stability of nanoparticles, achieves tumor targeting and sustained release, improves chemotherapy effects, and reduces damage to normal tissues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455009A_ABST
    Figure CN119455009A_ABST
Patent Text Reader

Abstract

The invention discloses a pH / GSH dual-responsive targeting nanoparticle based on MOF-199, the nanoparticle contains doxorubicin, MOF-199, polydopamine and hyaluronic acid, the doxorubicin is encapsulated in a pore structure of the MOF-199, the surface of the MOF-199 is coated with the polydopamine, and the polydopamine and the hyaluronic acid are grafted through a metal coordination effect. The invention also discloses a preparation method of the nanoparticle, the prepared nanoparticle has tumor targeting property, slow release property and pH / GSH responsive intelligent drug release ability, and also has high biocompatibility and stability, realizes organic combination of chemotherapy / chemical kinetic therapy (CDT) / photo-thermal therapy (PTT), makes up for the deficiency of traditional single therapy, and has broad application prospects. The compound has a great application prospect in preparation of anti-tumor drugs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedicine and relates to a pH / glutathione (GSH) dual-responsive targeted nanoparticle based on metal organic framework (MOFs) MOF-199 and a preparation method thereof. Background Art

[0002] Since chemotherapy will inevitably cause side effects, such as hair loss, chemotherapy-induced peripheral neuropathy, cardiotoxicity, diarrhea, infertility, etc., scientific researchers have explored many new therapies, such as simple, easy-to-operate and non-invasive photothermal therapy (PTT) and chemodynamic therapy (CDT). The vigorous development of smart nano drug carriers has solved the problems of nonspecific distribution and drug burst release. At the same time, in recent years, multimodal combined treatments such as chemotherapy combined with phototherapy have also become a research hotspot in the field of biomedicine. The high specific surface area and high porosity make the metal organic framework MOF-199 have good drug loading capacity. MOF-199 can consume glutathione (GSH) in cancer cells, and the synthesis method is simple. In recent years, it has been favored by researchers in the field of drug delivery. However, MOFs are easily combined with biological molecules, resulting in premature clearance by living organisms, and poor stability in the body. In order to increase the specific accumulation of drugs at the lesion site, surface chemical modification of MOFs after synthesis is very critical.

[0003] Based on this, the present invention adopts an innovative strategy, namely, modifying the MOF-199 surface with hyaluronic acid (HA) and using pH-sensitive polydopamine (PDA) membrane as the surface coating material of the drug carrier. This ingenious design not only gives the nanoparticles excellent active targeting properties, but also greatly enhances their biocompatibility and structural stability. Through these carefully designed steps, we have successfully constructed a comprehensive and excellent targeted nano drug delivery system. Summary of the invention

[0004] The purpose of the present invention is to provide an intelligent drug-releasing nanoparticle suitable for tumor chemotherapy / chemodynamic therapy (CDT) / photothermal therapy (PTT).

[0005] The technical solution of the present invention is as follows:

[0006] The present invention first provides a pH / GSH dual-responsive targeted nanoparticle based on MOF-199, wherein the nanoparticle contains doxorubicin, MOF-199, polydopamine and hyaluronic acid, wherein the doxorubicin is encapsulated in the pore structure of MOF-199, and the polydopamine is coated on the surface of MOF-199 and grafted with the hyaluronic acid through metal coordination.

[0007] The main functions of each component in the present invention are as follows:

[0008] Doxorubicin: a broad-spectrum anticancer drug.

[0009] MOF-199: The particle size is about 100nm and the morphology is uniform, which is suitable for use as a drug carrier. It uses its own porous characteristics to achieve drug encapsulation. More importantly, the Cu in MOF-199 2+ It can undergo redox reactions with GSH, thereby destroying the metabolic balance inside cancer cells. MOF-199 can also catalyze H2O2 to generate toxic hydroxyl radicals (·OH), helping to kill cancer cells.

[0010] Polydopamine: Taking advantage of the fact that dopamine hydrochloride undergoes self-polymerization under alkaline conditions, the bionic material polydopamine (PDA) is coated on the surface of the original carrier MOF-199 to block the pores of the metal organic framework. The pH-sensitive PDA coating remains stable in the neutral environment of healthy cells, but will fall off the surface of the material in the acidic environment of cancer cells, avoiding the release of contents in non-target areas and damage to healthy tissues and cells. In addition, the introduction of PDA can also increase the absorption of near-infrared light by nanoparticles, bringing about a photothermal effect.

[0011] Hyaluronic acid: It gives nanoparticles active targeting ability to tumor cells and improves the biocompatibility and stability of nanoparticles.

[0012] The present invention further provides a method for preparing the nanoparticles. First, the cancer therapeutic agent doxorubicin (DOX) is encapsulated in the metal organic framework MOF-199 by physical adsorption using the GSH-responsive nanocarrier MOF-199; then, a pH-sensitive polydopamine (PDA) membrane is used as a surface wrapping material to cover the surface of the nano drug carrier, thereby playing a "sealing" role, preventing the drug and the carrier from being lost before reaching the lesion, and reducing the risk of adverse reactions to healthy tissues and cells; finally, hyaluronic acid (HA) with a targeting function is grafted to the surface of DOX@MIL-199-PDA through the coordination effect of Fe3+.

[0013] The specific preparation process of DOX@MOF-199-PDA-HA is as follows:

[0014] 1) adding triethylamine and MOF-199 to an aqueous solution of doxorubicin hydrochloride, and stirring after ultrasonic treatment to obtain drug-loaded MOF-199 encapsulating doxorubicin (DOX@MOF-199);

[0015] 2) The drug-loaded MOF-199 is dispersed in Tris-HCl buffer, and then dopamine hydrochloride is added to polymerize dopamine to generate polydopamine, which is then coated on the surface of the drug-loaded MOF-199 to obtain drug-loaded MOF-199 coated with polydopamine (DOX@MOF-199-PDA);

[0016] 3) Disperse the drug-loaded MOF-199 coated with polydopamine in Tris-HCl buffer, then add FeCl3 and hyaluronic acid to 3+ The hyaluronic acid was grafted onto the surface of the drug-loaded MOF-199 coated with polydopamine by the coordination effect of , and the drug-loaded MOF-199 (DOX@MOF-199-PDA-HA) coated with polydopamine and grafted with hyaluronic acid on the surface was obtained.

[0017] The mass ratio of MOF-199 to doxorubicin hydrochloride is 0.5-2:1, preferably 1-1.5:1.

[0018] Wherein, the mass ratio of the drug-loaded MOF-199 to dopamine hydrochloride is 0.5-3:1, preferably 1.5-2.5:1.

[0019] The mass ratio of the drug-loaded MOF-199 encapsulating polydopamine to hyaluronic acid is 0.5-2:1, preferably 1-1.5:1.

[0020] The amount of FeCl3 used is 1-10% of the mass of the drug-loaded MOF-199 encapsulating polydopamine, preferably 3-6%.

[0021] Preferably, the stirring and encapsulating time is 3-6 hours.

[0022] Preferably, the pH of the Tris-HCl buffer is 7-10.

[0023] The test results show that: (1) the nanoparticles prepared by the present invention have high drug loading rate and encapsulation rate, with a DOX loading rate of about 40% and an encapsulation rate of about 70%, a spherical shell-core structure, an average particle size of about 120nm, a hydrated particle size of 270nm, and good dispersibility in water;

[0024] (2) Possessing the ability to consume GSH;

[0025] (3) It has the ability to catalyze the production of hydroxyl free radicals in vitro, and in an acidic and GSH microenvironment, the catalytic production of hydroxyl free radicals is more and time-dependent;

[0026] (4) It has a sustained release effect, especially under GSH, NIR irradiation and acidic conditions, which is more conducive to the release of DOX.

[0027] It can be seen that the present invention uses MOF-199 to encapsulate the broad-spectrum anticancer drug doxorubicin and prepare nanoparticles. On the one hand, doxorubicin has a sustained release effect, can reduce the sudden release of the drug, and prolong the drug's action time. In addition, the release of doxorubicin is easier to carry out under the conditions of GSH, acidity and NIR irradiation. This discovery enables doxorubicin to better target tumor cells for chemotherapy, which is beneficial to improve the chemotherapy effect and reduce damage to normal tissues. It is also suitable for photothermal therapy (PTT). On the other hand, the nanoparticles prepared by the present invention can undergo redox reactions with endogenous GSH of cancer cells, thereby destroying the metabolic balance inside cancer cells, and can catalyze the generation of hydroxyl radicals in the acidic and GSH microenvironment of the tumor, thereby killing cancer cells and achieving chemokinetic therapy (CDT) of the tumor.

[0028] In summary, the nanoparticles prepared by the present invention have tumor targeting, sustained release, and pH / GSH-responsive intelligent drug release capabilities, and also have high biocompatibility and stability, realizing the organic combination of chemotherapy / chemodynamic therapy (CDT) / photothermal therapy (PTT), making up for the shortcomings of traditional single therapy, and have great application prospects in the preparation of anti-tumor drugs. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 : In vitro drug release curve of DOX@MOF-199-PDA-HA in acidic medium.

[0030] Figure 2 : TEM images and particle size distribution of DOX@MOF-199 and DOX@MOF-199-PDA-HA. (A) is the TEM image of DOX@MOF-199, (B) is the TEM image of DOX@MOF-199-PDA-HA, (C) is the particle size distribution of DOX@MOF-199, and (D) is the particle size distribution of DOX@MOF-199-PDA-HA.

[0031] Figure 3 :Responsiveness test of DOX@MOF-199-PDA-HA and GSH. (A) is the UV absorption spectrum of DTNB after adding different concentrations of GSH; (B) is the UV absorption spectrum of DTNB after adding different concentrations of DOX@MOF-199-PDA-HA.

[0032] Figure 4 : The ultraviolet absorption spectrum of DOX@MOF-199-PDA-HA catalyzed in vitro generation of hydroxyl radicals was investigated using TMB reagent.

[0033] Figure 5:The effect of in vitro environment on the generation of hydroxyl radicals by DOX@MOF-199-PDA-HA. (A) is the UV absorption spectrum of ox-TMB under different pH and GSH environments; (B) is the UV absorption of ox-TMB at different times.

[0034] Figure 6 :In vitro release curves of DOX@MOF-199-PDA-HA. (A) is the in vitro release curve under different pH and GSH conditions; (B) is the in vitro release curve under NIR irradiation conditions. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments.

[0036] Example 1: Preparation of DOX@MOF-199-PDA-HA

[0037] Step 1: Preparation of DOX@MOF-199

[0038] Prepare doxorubicin hydrochloride aqueous solution, add 70 μL triethylamine to 35 mL DOX·HCl aqueous solution (2 mg / mL), and ultrasonicate for 3 min. Then take 120 mg MOF-199 and add it to the above solution and disperse it evenly. After ultrasonication for 10 min, place it in a magnetic stirrer and stir it in the dark for 5 h, centrifuge and wash to obtain DOX@MOF-199.

[0039] Step 2: Synthesis of DOX@MOF-199-PDA

[0040] Prepare a Tris-HCl buffer solution with a pH value of 9.5, take 50 mg of DOX@MOF-199 and ultrasonically disperse it in 50 mL of Tris-HCl (10 mM) buffer solution. Then add 75 mg of dopamine hydrochloride and react for 6 hours in the dark. Separate by centrifugation (8000 rpm) and wash with deionized water several times to obtain a black solid product, namely DOX@MOF-199-PDA.

[0041] Step 3: Synthesis of DOX@MOF-199-PDA-HA

[0042] 50 mg of DOX@MOF-199-PDA was dispersed in 50 mL of Tris-HCl buffer solution (pH 9.5), and 1 mg of FeCl3 solution was added and stirred for 1 hour. Subsequently, 75 mg of HA was added and mixed, and the mixture was stirred and reacted for 5 hours under light-proof conditions. After the reaction was terminated, the mixed nanoparticles were collected by centrifugation and repeatedly washed with pure water, and finally freeze-dried at -60 ° C to obtain the black solid product, which was DOX@MOF-199-PDA-HA.

[0043]

[0044] Example 2: Preparation of DOX@MOF-199-PDA-HA

[0045] Step 1: Synthesis of DOX@MOF-199

[0046] Prepare doxorubicin hydrochloride aqueous solution, add 70 μL triethylamine to 35 mL DOX·HCl aqueous solution (2 mg / mL), and ultrasonicate for 3 min. Take 75 mg MOF-199 and add it to the above solution and disperse it evenly. After ultrasonication for 10 min, place it in a magnetic stirrer and stir it in the dark for 4 h, centrifuge and wash to obtain DOX@MOF-199.

[0047] Step 2: Synthesis of DOX@MOF-199-PDA

[0048] Prepare a Tris-HCl buffer solution with a pH value of 8.5, take 50 mg of DOX@MOF-199 and ultrasonically disperse it in 50 mL of Tris-HCl buffer solution. Then add 25 mg of dopamine hydrochloride and react for 4 hours in the dark. After centrifugation and washing with deionized water for several times, a black solid product, DOX@MOF-199-PDA, is obtained.

[0049] Step 3: Synthesis of DOX@MOF-199-PDA-HA

[0050] 50 mg of DOX@MOF-199-PDA was dispersed in 50 mL of Tris-HCl buffer solution (pH 8.5), and 2.5 mg of FeCl3 solution was added and stirred for 1 hour. Subsequently, 50 mg of HA was added and mixed, and the reaction was stirred for 4 hours under light-proof conditions. After the reaction was terminated, the nanoparticles were collected by centrifugation and repeatedly washed with pure water, and finally freeze-dried at -60 ° C to obtain a black solid product, which was DOX@MOF-199-PDA-HA.

[0051] Example 3: Preparation of DOX@MOF-199-PDA-HA

[0052] Step 1: Synthesis of DOX@MOF-199

[0053] Prepare doxorubicin hydrochloride aqueous solution, add 70 μL triethylamine to 35 mL DOX·HCl aqueous solution (2 mg / mL), and ultrasonicate for 3 min. Take 50 mg MOF-199 and add it to the above solution and disperse it evenly. After ultrasonication for 10 min, place it in a magnetic stirrer and stir it in the dark for 3 h, centrifuge and wash to obtain DOX@MOF-199.

[0054] Step 2: Synthesis of DOX@MOF-199-PDA

[0055] Prepare a Tris-HCl buffer solution with a pH value of 7.5, take 50 mg of DOX@MOF-199 and ultrasonically disperse it in 50 mL of Tris-HCl buffer solution. Then add 50 mg of dopamine hydrochloride and react for 2.5 hours in the dark. After centrifugation and washing with deionized water for several times, a black solid product, DOX@MOF-199-PDA, is obtained.

[0056] Step 3: Synthesis of DOX@MOF-199-PDA-HA

[0057] 50 mg of DOX@MOF-199-PDA was dispersed in 50 mL of Tris-HCl buffer solution (pH 7.5), and 5 mg of FeCl3 solution was added and stirred for 1 hour. Subsequently, 25 mg of HA was added and mixed, and the reaction was stirred for 3 hours under light-proof conditions. After the reaction was terminated, the nanoparticles were collected by centrifugation and repeatedly washed with pure water, and finally freeze-dried at -60 ° C to obtain a black solid product, which was DOX@MOF-199-PDA-HA.

[0058] Example 4: Preparation of DOX@MOF-199-PDA-HA

[0059] Step 1: Synthesis of DOX@MOF-199

[0060] Prepare doxorubicin hydrochloride aqueous solution, add 70 μL triethylamine to 35 mL DOX·HCl aqueous solution (2 mg / mL), and ultrasonicate for 3 min. Take 100 mg MOF-199 and add it to the above solution and disperse it evenly. After ultrasonication for 10 min, place it in a magnetic stirrer and stir it in the dark for 6 h, centrifuge and wash to obtain DOX@MOF-199.

[0061] Step 2: Synthesis of DOX@MOF-199-PDA

[0062] Prepare a Tris-HCl buffer solution with a pH value of 8.0, take 50 mg of DOX@MOF-199 and ultrasonically disperse it in 50 mL of Tris-HCl buffer solution. Then add 100 mg of dopamine hydrochloride and react for 3 hours in the dark. After centrifugation and washing with deionized water for several times, a black solid product, DOX@MOF-199-PDA, is obtained.

[0063] Step 3: Synthesis of DOX@MOF-199-PDA-HA

[0064] 50 mg of DOX@MOF-199-PDA was dispersed in 50 mL of Tris-HCl buffer solution (pH 7.5), and 3 mg of FeCl3 solution was added and stirred for 1 hour. Subsequently, 100 mg of HA was added and mixed, and the reaction was stirred for 1 hour under light-proof conditions. After the reaction was terminated, the nanoparticles were collected by centrifugation and repeatedly washed with pure water, and finally freeze-dried at -60 ° C to obtain a black solid product, which was DOX@MOF-199-PDA-HA.

[0065] Test example

[0066] 1. Determination of drug loading rate and encapsulation efficiency

[0067] Prepare 5-50μg / mL standard aqueous solution of doxorubicin drug and make a standard curve of the drug. The encapsulation efficiency of the drug-carrying system is obtained by dividing the amount of DOX loaded by DOX@MOF-199-PDA-HA by the amount of DOX drug originally input. That is, the encapsulation efficiency (EE%) of nano-doxorubicin is calculated as follows: encapsulation efficiency (DEE%) = (total amount of DOX - free amount of DOX) / total amount of DOX * 100%. Drug loading rate (DLC%) = (total amount of DOX - free amount of DOX) / total mass of nanoparticles. Accurately prepare and measure 1mL of DOX@MOF-199-PDA-HA solution, centrifuge it twice at 10000rpm in the inner tube of the ultrafiltration tube (molecular weight cutoff 3kDa), and collect the free DOX in the outer tube of the ultrafiltration tube. Dilute to 10 mL with anhydrous methanol, take 0.5 mL and dilute to 3 mL, use UV spectrophotometer to detect its absorbance, calculate the drug content in the sample, and finally use the formula to calculate the drug loading rate and encapsulation rate of DOX@MOF-199-PDA-HA in each example:

[0068] Table 1 Results of drug loading and encapsulation efficiency of nanoparticles

[0069] Drug loading rate Encapsulation efficiency Example 1 25.73% 56.39% Example 2 39.58% 73.26% Example 3 32.24% 66.85% Example 4 27.67& 59.88%

[0070] In addition, by testing the in vitro drug release rate of DOX@MOF-199-PDA-HA prepared in Example 2 under acidic conditions, it was found that the drug release in Example 2 was more sufficient and the sustained release effect was better ( Figure 1 ), so we chose the conditions in Example 2 as the optimal process conditions and continued to carry out experiments on this basis.

[0071] 2. Structural Characterization

[0072] like Figure 2As shown in A, the TEM image intuitively shows the octahedral morphology of DOX@MOF-199. As one of the typical porous cage-channel structure metal-organic frameworks (MOFs), MOF-199 has a particle size of about 100 nm. However, since the core component of MOF-199 contains divalent copper ions, direct application in drug carriers may pose potential toxicity to organisms. Therefore, we introduced the biomimetic material polydopamine (PDA) for surface modification to improve the biocompatibility of the carrier. Figure 2 As shown in Figure B, the TEM image reveals that the surface of the modified DOX@MOF-199-PDA-HA is covered with a fuzzy transparent layer, the morphology changes to a spherical shape, forming an obvious core-shell structure, and the particle size increases to about 120 nm.

[0073] Furthermore, DLS testing provides important information on the particle size distribution and dispersion state of these materials in aqueous solutions, such as Figure 2 C and Figure 2 As shown in Figure D, the results show that the average hydrated particle size of DOX@MOF-199 is 210nm, while the average hydrated particle size of DOX@MOF-199-PDA-HA increases to 303nm, an increase of about 90nm. In addition, the dispersion coefficients PDI of the two are 0.119 and 0.172, respectively. Although the particle size of the carrier increases after surface modification, it still maintains good dispersibility, which is crucial for the stability and efficacy of the drug delivery system.

[0074] Through the combined analysis of TEM and DLS, we not only confirmed the morphological and size changes of MOF-199 and its modified products, but also verified that PDA surface modification not only improved the biosafety of MOF-199, but also effectively regulated its particle size and dispersibility in aqueous solution, laying the foundation for subsequent drug loading and targeted delivery.

[0075] 3. GSH responsiveness assay

[0076] The performance of DOX@MOF-199-PDA-PDA in consuming GSH was tested. 5,5'-Dithiobis(2-nitrobenzoic acid) (DTNB) reagent was used to explore the release of Cu from DOX@MOF-199-PDA-HA. 2+GSH consumption caused by. When pH = 5, the prepared DOX@MOF-199-PDA-HA solution was mixed with different concentrations of GSH (0, 2, 5, 10 and 15mM), and the mixed liquid was allowed to stand at room temperature for 30 minutes. Then, an appropriate amount of supernatant was collected using a centrifuge, and the DTNB reagent was added to react for 5 minutes, and the change in absorbance was measured by a UV spectrophotometer. At the same time, another experimental group was set up, and different concentrations of DOX@MOF-199-PDA-HA (20, 50, 100, 200, 500mg / mL) were added to the solution containing GSH, and the rest of the operations were the same as above.

[0077] 5,5'-Dithiobis(2-nitrobenzoic acid) (DTNB) can undergo redox reaction with GSH, and generate yellow-appearing product 5-thio-2-nitrobenzoate (TNB), so the maximum absorption wavelength also changes from 325nm to 442nm. Therefore, we can use UV spectrometer to observe the change of sample absorbance and investigate the consumption of GSH. At pH 5, the UV absorption curve of DTNB after adding different concentrations of GSH is as follows: Figure 3 As shown in A, when GSH was not added, only one absorption peak at 325 nm appeared. When GSH was added, the absorption peak at 325 nm gradually disappeared, and a maximum absorption peak appeared at 442 nm, which proved that Cu in DOX@MOF-199-PDA-HA 2+ GSH has been consumed. Figure 3 As shown in (B), as the concentration of added MOF increases, the absorbance of DTNB at 442 nm gradually decreases, further indicating that DOX@MOF-199-PDA-HA has the ability to consume GSH.

[0078] 4. In vitro catalytic performance test of hydroxyl radical production

[0079] Hydroxyl radicals (·OH) can undergo redox reactions with colorless 3,3',5,5'-tetramethylbenzidine (TMB) to generate a blue product, ox-TMB. Therefore, the ability of DOX@MOF-199-PDA-HA to catalyze the generation of hydroxyl radicals (·OH) in vitro can be verified by observing the change in the absorbance value at the maximum absorption wavelength (650nm) of ox-TMB. First, DMSO was used as a solvent to prepare a 10mg / mL TMB solution, and then 2.5mg of DOX@MOF-199-PDA-HA was weighed and added to an acetate buffer solution with a pH of 5. After ultrasonic treatment, the solution was fixed to volume with a 25mL volumetric flask, and finally a uniformly dispersed DOX@MOF-199-PDA-HA (100μg / mL) test solution was obtained. 5 μL 30% H2O2 (providing the same conditions as the overexpressed H2O2 in the cancer cell site) and 20 μL TMB were added to the above test solution and mixed evenly, and then allowed to stand at room temperature for 5 minutes. Finally, the UV absorption of the sample was measured and recorded using a UV-2600 instrument. TMB+DOX@MOF-199-PDA-HA and TMB+30% H2O2 were set as control groups, and the rest of the steps were the same as the experimental group.

[0080] UV absorption spectrum Figure 4 As shown, the TMB+H2O2+DOX@MOF-199-PDA-HA sample group showed a strong absorption peak at 650nm, and the aqueous solution was blue. The TMB+DOX@MOF-199-PDA-HA and TMB+H2O2 groups did not show any absorption peak signal within the selected experimental wavelength range, and the sample aqueous solutions were still colorless. The above results confirm that DOX@MOF-199-PDA-HA has the function of catalyzing H2O2 to produce hydroxyl radicals, and ·OH can kill cancer cells, thereby completing CDT therapy.

[0081] 5. Effects of pH and GSH on the generation of hydroxyl radicals by DOX@MOF-199-PDA-HA in vitro

[0082] Prepare DOX@MOF-199-PDA-HA test solutions (100μg / mL) at pH=5, pH=6 and pH=7.4, and set up a control group with pH=5 and GSH (10mM) added. Measure 5μL H2O2 (30%) and 20μL TMB solution, and mix them with 3mL of the above different test solutions. After standing at room temperature for 5 minutes, record the ultraviolet absorption of different samples in the wavelength range of 200-800nm ​​and draw a spectrum. In addition, the ultraviolet absorption change spectrum of the control group in different minutes was also explored. This experiment investigated the generation of toxic OH by DOX@MOF-199-PDA-HA (100μg / mL) under different pH and GSH environments.

[0083] like Figure 5 As shown in (A), when the pH range is 5 to 7.4, the absorbance decreases with the increase of pH value, and there is no absorption peak at pH 7.4. This indicates that the smaller the pH, the greater the ultraviolet absorption intensity of ox-TMB with a maximum absorption wavelength of 650nm, that is, the more ·OH is produced. This shows that compared with the normal neutral physiological environment of the human body, MOF-199-PDA-HA is more inclined to produce toxic ·OH in an acidic environment. However, when the pH is 5 and 10mM GSH is added, the absorbance increases more significantly, far higher than the simple pH group, at which time the amount of toxic ·OH generated is the highest. This further illustrates that DOX@MOF-199-PDA-HA is very suitable for generating ·OH in cancer cells with acidic environments and high concentrations of GSH, thereby promoting the death of cancer cells. In addition, the ultraviolet absorption of ox-TMB in different minutes after pH = 5 and the addition of 10mM GSH was also recorded. From Figure 5 As can be seen in (B), the change in the absorbance of ox-TMB at 650nm is positively correlated with time. The longer the time, the greater the absorbance, which proves that DOX@MOF-199-PDA-HA consumes GSH to produce toxic ·OH with a time-dependent characteristic, which is also conducive to the effect of long-lasting treatment.

[0084] 6. In vitro drug release test of drug-carrying system DOX@MOF-199-PDA-HA

[0085] Different pH and GSH groups were set up to simulate the tumor microenvironment to verify that the drug-carrying system DOX@MOF-199-PDA-HA has pH sensitivity and GSH-responsive drug release characteristics. Buffered saline solutions of different pH (PBS, pH = 5, 6 and 7) were prepared, and 5 mg of DOX@MOF-199-PDA-HA was added to them respectively, and dispersed evenly at room temperature, and each pH group was tested in triplicate. The above dispersion was then placed in a dialysis bag (3500Da), and then the dialysis bag was transferred to a beaker and completely immersed in 25 mL of the corresponding PBS solution. The beaker was placed in a constant temperature incubator (37°C) and shaken (160rpm). Subsequently, at each time point of the experimental setting, 3 mL of supernatant was drawn with a dropper, and an equal amount of PBS solution of the same pH was supplemented. The supernatant A value measured by the UV-Vis spectrometer was substituted into the standard curve, and the cumulative drug release rate R% was obtained using the following formula. At the same time, two control groups (PBS buffer solution pH = 5 and pH = 7.4 groups, both with 10 mM GSH added) and two illumination groups (drug-loaded sample solutions were illuminated with a power of 2 W / cm 2 The rest of the experimental operation was the same as above. Compared with cells in normal organisms, tumor cells have a faster metabolism, and because they breathe anaerobicly, they can produce more lactic acid. Therefore, the pH of the cancer cell site is low and acidic, and there is a large amount of GSH. We set different pH and GSH to make the experimental conditions closer to the normal cell environment and the internal environment of the tumor, and at the same time explored the effect of NIR irradiation on the experiment.

[0086] like Figure 6 As shown in (A), in the range of pH 5 to 7.4, the drug release rate is negatively correlated with the pH value. The larger the pH, the smaller the total release rate. That is, DOX@MOF-199-PDA-HA has a stronger drug release ability under acidic conditions. Moreover, for the pH 7.4 group, regardless of whether GSH is added, the total drug release rate does not exceed 20%. Under the conditions of pH 5 and the addition of GSH, the total DOX release rate reached 58% at the 72nd hour and tended to a stable state, which was higher than the 44.65% of the pH = 5 group and the 13.23% of the pH = 7.4 group containing GSH. For the illumination group, the sample group with pH 5 containing or not containing GSH was placed in the NIR area and then its drug release was tested. As shown Figure 6As shown in (B), after NIR treatment, the total drug release rate of the sample group with pH 5 was higher than that before illumination. Among them, the total drug release rate of the illumination group containing GSH and pH = 5 was the largest and the increase was also the largest, indicating that GSH, NIR irradiation and acidic conditions are all conducive to the release of DOX. The drug release of DOX@MOF-199-PDA-HA in the tumor site will be greater than that in the normal site, because when DOX@MOF-199-PDA-HA enters the cancer cell with a lower pH, the PDA coating on the surface of the drug carrier will automatically fall off, exposing the internal metal organic framework. At this time, the BTC ligand in MOF-199 begins to protonate and binds to Cu 2+ The coordination effect of 2+ It immediately consumes a large amount of GSH in cancer cells. In addition, the amino groups in DOX are protonated under low pH conditions, and the adsorption force with MOF becomes weaker. These all cause the MOF-199 skeleton to collapse and the drug to be released. The above all indicate that this drug delivery system has pH and GSH responsive drug release functions, which can avoid drug leakage in normal tissues, and the loaded DOX is released more in cancer cells, thereby reducing toxic side effects on the body.

[0087] 7. Cytotoxicity Assay

[0088] In order to ensure that the drug carrier is harmless to the human body, an in vitro cytotoxicity analysis experiment was conducted. The blank drug carrier MOF-199-PDA-HA with different concentration gradients was incubated with MG-63 cells for 24 hours, and then the CCK-8 method was used to study the cytotoxicity of MOF-199-PDA-HA. The experimental results show that the survival rate of MG-63 cells treated with MOF-199-PDA-HA in a concentration range of 25-500μg / mL is above 90%, whether it is the experimental group or the illumination group treated with infrared light. With the increase of concentration, even when it reaches 500μg / mL, the inhibitory effect of the blank drug carrier on cells is not significantly enhanced. The above shows that the MOF-199-PDA-HA synthesized in this project itself has low toxicity and is suitable for drug delivery.

Claims

1. A pH / GSH dual-responsive targeting nanoparticle based on MOF-199, characterized in that: The nanoparticles contain doxorubicin, MOF-199, polydopamine and hyaluronic acid. The doxorubicin is encapsulated in the pore structure of MOF-199, and the polydopamine is coated on the surface of MOF-199 and grafted with the hyaluronic acid through metal coordination.

2. A method for preparing the pH / GSH dual-responsive targeting nanoparticles according to claim 1, characterized in that The following steps are involved: 1) adding triethylamine and MOF-199 to an aqueous solution of doxorubicin hydrochloride, and stirring after ultrasonic treatment to obtain drug-loaded MOF-199 encapsulating doxorubicin; 2) dispersing the drug-loaded MOF-199 in Tris-HCl buffer, and then adding dopamine hydrochloride to polymerize dopamine to generate polydopamine, which is then coated on the surface of the drug-loaded MOF-199, thereby obtaining drug-loaded MOF-199 coated with polydopamine; 3) Disperse the drug-loaded MOF-199 coated with polydopamine in Tris-HCl buffer, then add FeCl3 and hyaluronic acid to 3+ The hyaluronic acid is grafted onto the surface of the drug-loaded MOF-199 coated with polydopamine by the coordination effect, thereby obtaining the drug-loaded MOF-199 coated with polydopamine and grafted with hyaluronic acid on the surface.

3. The preparation method according to claim 2, characterized in that: The mass ratio of MOF-199 to doxorubicin hydrochloride is 0.5-2:1, preferably 1-1.5:

1.

4. The preparation method according to claim 2, characterized in that: The mass ratio of the drug-loaded MOF-199 to dopamine hydrochloride is 0.5-3:1, preferably 1.5-2.5:

1.

5. The preparation method according to claim 2, characterized in that: The mass ratio of the drug-loaded MOF-199 coated with polydopamine to hyaluronic acid is 0.5-2:1, preferably 1-1.5:

1.

6. The preparation method according to claim 2, characterized in that: The amount of FeCl3 used is 1-10% of the mass of the drug-loaded MOF-199 coated with polydopamine, preferably 3-6%.

7. The preparation method according to claim 2, characterized in that: The stirring time is 3-6h.

8. The preparation method according to claim 2, characterized in that: The pH of the Tris-HCl buffer is 7-10.

9. Use of the nanoparticles according to claim 1 in the preparation of anti-tumor drugs.

10. The use according to claim 9, characterized in that: The nanoparticles have tumor targeting, sustained release, and pH / GSH-responsive intelligent drug release capabilities, and are used for combined chemotherapy / chemodynamic therapy / photothermal therapy of tumors.

Citation Information

Patent Citations

  • Multifunctional drug delivery system based on dopamine-coated metal organic framework derivative and preparation method of multifunctional drug delivery system

    CN116585288A

  • Active targeting nano-drug for treating breast cancer as well as preparation method and application of active targeting nano-drug

    CN118436805A